2018
DOI: 10.1097/ccm.0000000000003071
|View full text |Cite
|
Sign up to set email alerts
|

Sedation Intensity in the First 48 Hours of Mechanical Ventilation and 180-Day Mortality: A Multinational Prospective Longitudinal Cohort Study*

Abstract: Sedation intensity independently, in an ascending relationship, predicted increased risk of death, delirium, and delayed time to extubation. These observations suggest that keeping sedation level equivalent to a Richmond Agitation Sedation Scale 0 is a clinically desirable goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
138
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(152 citation statements)
references
References 24 publications
7
138
1
6
Order By: Relevance
“…The main information to remember is that the use of sedation increases the risk of delirium; both the depth and kind of sedation are of importance, which has been confirmed by the study carried out by Shehabi et al in 2018 [39]. The study included more than 700 patients and analysed the depth of sedation during the first 48 hours of ICU treatment versus the incidence of delirium, possible early extubation and 180-day mortality.…”
Section: Choice Of Sedation and Development Of Deliriummentioning
confidence: 90%
See 1 more Smart Citation
“…The main information to remember is that the use of sedation increases the risk of delirium; both the depth and kind of sedation are of importance, which has been confirmed by the study carried out by Shehabi et al in 2018 [39]. The study included more than 700 patients and analysed the depth of sedation during the first 48 hours of ICU treatment versus the incidence of delirium, possible early extubation and 180-day mortality.…”
Section: Choice Of Sedation and Development Of Deliriummentioning
confidence: 90%
“…According to the authors, irrespective of other factors, a deeper level of sedation increases the risk of death (HR [95% CI] 1.29 [1. 15-1.46]; P < 0.001) and the risk of delirium (HR [95% CI] 1.25 [1.10-1.43]; P = 0.001) while decreasing the possibility of early extubation (HR [95% CI] 0.80 [0.73-0.87]; P < 0.001) [39]. The authors conclude that, since the depth of sedation is an independent risk factor of death, delirium and delayed extubation in the ICU, the targeted level of sedation to achieve should be a RASS score of 0.…”
Section: Choice Of Sedation and Development Of Deliriummentioning
confidence: 99%
“…Sedation with γ-aminobutyric acid agonists, for example, is a common risk factor for delirium during critical illness. 40 In the current trial, approximately 90% of the patients received one or more doses of sedatives or analgesics, and the doses of sedatives and offtrial antipsychotic medications and the durations of exposures to those agents were similar in all trial groups. Most patients in the trial had hypoactive delirium, which made it difficult to estimate the effect of antipsychotic medications on Shown are Kaplan-Meier curves of the probability of survival.…”
Section: Discussionmentioning
confidence: 70%
“…The most important factor may be the difference in sedation levels. Patients in the control group received light sedation according to the current guidelines [10,11,29,30], in the ROSE trial, however, those patients received deep sedation in other previous published studies. It has been reported that deep sedation use in critically ill patients is independently associated with delayed extubation and increased mortality [31].…”
Section: Discussionmentioning
confidence: 99%